Effects of nitrogen and phosphorus fertilizer application rates on phytic acid content in barley grains - MAO Ying; CHEN Xin; QIU Bo-yin; WU Fei-bo; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版, 2009)
A field experiment with split-plot design was carried out to study the effect of three N levels and three P levels on phytic acid as well as protein and total phosphorus contents of two barley cultivars. The results show that phytic acid content was reduced significantly with increasing N level, and the hullless variety CAW192 was more changed than the hulled variety ZAU3 by N level, though the former had lower phytic acid content. The effect of P application level on phytic acid was also detected, and the extent of the effect differed greatly between the two varieties. ZAU 3 had the highest phytic acid content in the moderate P level, with the difference being significant among three P levels. However, no significant difference was found among three P levels for CAW192. There was a significant interaction between N and P levels in their effect on phytic acid content, and higher P level may alleviate the effect of N fertilizer on phytic acid content. The correlation analysis show that phytic acid content was not correlated with grain protein content. The correlation between P and phytic acid contents differed between the two varieties, with ZAU3 being significant, and CAW192 no significant, suggesting that the relationship between phytic acid and P contents in barley grain is genotype-dependent.